The influence of athlete role models on youngsters, in terms of motivation and involvement in sports - Γκικνούρη, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2022)
The purpose of the present study is to present the importance of the role of the elite athletes, specifically those who participated in the Olympic Games or excelled in championships and world championships for young children for their involvement in sports. It aims to investigate the relationship that is created between athletes and younger generation and what is the impact of the victories of those athletes for children and their future choices. Are the achievements of an athlete that make him stand out among thousands of other athletes? Is it the behavior that an athlete shows during the game in the sports field that can have an impact? Is there any correlation between the so called heroes of the ancient time athletes and the today’s athlete role models? This paper work has tried to answer questions like these, by conducting a research as part of the master’s degree thesis. The study was carried out through interviews of twenty six Greek athletes and the results were rather unexpected according to researcher’s first belief. The analysis of the results showed that there is indeed a good correlation between the athletes who inspire and the involvement of young children in sports, but not such a strong link that can affect them and / or influence them on which sport they will choose to practice. Of course, for safer results and more accurate data, deeper research (for example PhD) is suggested for data-based arguments.
Keywords: Olympism; Olympic education; Athletes; Role models; Ολυμπισμός; Ολυμπιακή παιδεία; Αθλητές; Πρότυπα; Olympism; Role models; Olympic education; Athletes; Youth